2017
DOI: 10.5539/jsd.v10n1p156
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Agriculture Promotion and Uptake in Mufulira, Zambia-A Political Agronomy Approach

Abstract: This study utilized 120 semi-structured interviews with smallholder farming households and two focus group discussions; as well as several key informant interviews with experts to explore the promotion and uptake of conservation agriculture (CA) in Mufulira, Zambia. Results reveal that ridges and flat culture continued to be the preferred tillage systems (97 per cent and 55 per cent respectively) despite the farmers having been trained in the use of a minimum tillage technique. None of the interviewed farmers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Contestations exist surrounding performance of CA under smallholder farming conditions (Baudron, Andersson, Corbeels, & Giller, 2011;Giller, Witter, Corbeels, & Tittonell, 2009;Giller et al, 2015;Pittelkow et al, 2015). In addition, lack of consensus regarding universal definition of CA (Glover, Sumberg, & Andersson, 2016;Whitfield et al, 2015) has led to diverse interpretations and promotion of disparate practices in different countries (Andersson & D'Souza, 2014;Bwalya Umar, 2017;Grabowski & Kerr, 2014;Kassam et al, 2012;Kirkegaard et al, 2014) Government, 2016) and coupled with the smallholders' tradition of growing maize .…”
mentioning
confidence: 99%
“…Contestations exist surrounding performance of CA under smallholder farming conditions (Baudron, Andersson, Corbeels, & Giller, 2011;Giller, Witter, Corbeels, & Tittonell, 2009;Giller et al, 2015;Pittelkow et al, 2015). In addition, lack of consensus regarding universal definition of CA (Glover, Sumberg, & Andersson, 2016;Whitfield et al, 2015) has led to diverse interpretations and promotion of disparate practices in different countries (Andersson & D'Souza, 2014;Bwalya Umar, 2017;Grabowski & Kerr, 2014;Kassam et al, 2012;Kirkegaard et al, 2014) Government, 2016) and coupled with the smallholders' tradition of growing maize .…”
mentioning
confidence: 99%
“…Crop rotations involving at least one legume, the use of crop residues, and timely planting emerged as the three most important SLM strategies used by rural households in the Eastern Province. These are three of the practices of the "CA package" promoted among smallholder farmers in Zambia [42,80]. Previous studies suggested that farmers opt for crop rotations because of the benefits associated with pests and disease control and food diversification [78].…”
Section: Discussionmentioning
confidence: 99%